# math

posted by .

Differentiate, do not simplify.
a) y=(3x+2)(x^2-7)
b) x^3+3y^2=36

• math -

Go on: wolframalpha dot com

When page be open in rectangle type:

derivative (3x+2)(x^2-7)

and click option =

After few seconds when you see result click option:

Show steps

Then in rectangle type:

derivative x^3+3y^2=36

and click option =

After few seconds when you see result click option:

Show steps

## Similar Questions

1. ### trigo help!

1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)
2. ### math

Express y=[4x-x^3]/[3x^2+2)^2 as a product and then differentiate. Simplify your answer using positive exponents. Help Please! ty
3. ### calculus

I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the chain …
4. ### MATH

9√x/x a) rewrite b)differentiate c)simplify
5. ### MATH

y = 2/x^-8 rewrite differentiate simplify
6. ### math-check

I have solved the following questions, let me know if they are correct, thanks. 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 …
7. ### math

I have solved the following questions, let me know if they are correct, thanks. 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 …
8. ### Math

1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 + 4e^x)^5 answer: 20e^x (3+ 4ex)^4 c. y= (e^x - 1) / x^2 answer: (xe^x - 2e^x …
9. ### Math

1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 + 4e^x)^5 answer: 20e^x (3+ 4ex)^4 c. y= (e^x - 1) / x^2 answer: (xe^x - 2e^x …
10. ### Math

I have solved the following and I am writing just their answers with it, please let me know if these are correct. thanks 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify y= (e^x - …

More Similar Questions